EFFECTS OF A 980-NM DIODE LASER’S ACTIVATION OF 2.5% NAOCL AND 2% CHLORHEXIDINE ANTIFUNGAL IRRIGATION SOLUTIONS ON CANDIDA ALBICANS BIOFILMS - Iselinni, Chitra; Meidyawati, Ratna; Djauharie, Nilakusuma (International Journal of Applied Pharmaceutics, 2018)
Objective: Candida albicans is the most frequently found fungi in persistent root canal infections; it can form a biofilm and penetrate into dentinal tubules. Endodontic irrigants, such as 2.5% sodium hypochlorite (NaOCl) and 2% chlorhexidine (CHX), have antifungal properties, but limited penetration into dentinal tubules, which somewhat protects the C. albicans fungi. The use of a diode laser is an innovative approach in root canal treatments because it is able to penetrate deeper into the dentinal tubules. This study examined the effect of a 980-nm diode laser on the antifungal properties of 2.5% NaOCl and 2% CHX on C. albicans biofilms. Methods: The number of C. albicans colonies in the biofilms was recorded after irrigation using 2.5% NaOCl and 2% CHX. Then, the biofilms were radiated using a 980-nm diode laser. Results: Showed statistically significant differences between the use of the irrigants only and the use of the irrigants plus the diode laser treatment in the reduction of the C. albicans colonies in the biofilm. Conclusion: Diode laser is able to activate the antifungal properties of the 2.5% NaOCl and 2% CHX endodontic irrigants.